Audit Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5 (Studi Kasus : Badan Narkotika Nasional Provinsi Bali) - Martika, Putu Wahyu Novian; Gita, Dwi Putra; Raharja, I Made Sunia (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 1 (2022): JITTER, Vol.3, No.1, April 2022, 2022)
One of the organizations requiring the implementation of good IT governance is BNNP Bali. This audit is conducted to determine the level of IT process capability based on COBIT 5 standard to know the level of gap (GAP) owned by BNNP Bali. The process of conducting the audit begins by making observations in the environment related institutions and activities of data implementation and then carried out from the data is mapping with business goals according to COBIT 5, followed by mapping business goals with IT goals to obtain IT process. The acquired IT process is then selected to get an important IT process according to company officials. The process of IT obtained then performed data processing that is by using guttman method. Results of the capability level of the IT process ie EDM01, EDM02 and APO09 are at level 3 (Establised). The GAP found need to be given improvement strategy to achieve the expected capability of the institution that is 4 (predictable process) by providing recommendations related steps to achieve the expected capability value. Recommendations and improvements provided using ISO / IEC 15504: 2 2003 and ISO27002 standards obtained by mapping the IT process on COBIT 5.